2007
DOI: 10.1007/bf02940315
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological variation of primary mucosa-associated lymphoid tissue lymphoma of the oral cavity

Abstract: Primary mucosa-associated lymphoid tissue (MALT) type lymphoma arising in the oral cavity is rare. We examined histopathologic, immunohistological and genotypic findings of seven cases of intraoral MALT lymphoma using formalin-fixed paraffin-embedded tissues. Histologically, two variants have been delineated. (i) In four cases of minor salivary gland type, the lymphoid follicles were surrounded by centrocyte-like (CCL) cells with occasional follicular colonization. The CCL cells invaded the residual salivary g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Medical records of these 30 cases were extensively reviewed. Six cases have been reported previously [8,17].…”
Section: Methodsmentioning
confidence: 95%
“…Medical records of these 30 cases were extensively reviewed. Six cases have been reported previously [8,17].…”
Section: Methodsmentioning
confidence: 95%
“…However, the present case indicated that MZBL should be added to the differential diagnosis of IMT of the soft tissue. Both IMT arising from buccal mucosa and primary buccal mucosa MZBL appear to be rare disorders [2,3,11]. However, it is important to discriminate MZBL and IMT on clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…Kojima and colleagues reported that MALT lymphoma occurred in the soft palate and recurred [6,15]. This MALT lymphoma showed positivity for kappa but negativity for CD5.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary gland and thyroid MALT lymphomas are associated with autoimmune disorders such as Sjogren's syndrome and Hashimoto disease, respectively [4,5]. Primary MALT lymphomas can also occur in the oral cavity, although their appearance in this location is rare [6]. …”
Section: Introductionmentioning
confidence: 99%